PENGARUH MODEL PEMBELAJARAN PROBLEM-BASED LEARNING (PBL) BERBASIS LITERASI TERHADAP MINAT MEMBACA SISWA KELAS V DALAM MATA PELAJARAN BAHASA INDONESIA DI SD NEGERI 9 SONGAN KINTAMANI - Ni Kadek Ariantini; Ni Made Anggreni; Ni Nyoman Ayu Suciartini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of a literacy-based Problem-Based Learning (PBL) model on the reading interest of fifth-grade students in the Indonesian Language subject at SD Negeri 9 Songan, Kintamani. This study was motivated by the low reading interest among students, which is caused by a lack of variety in teaching models and the suboptimal implementation of literacy activities at the school. This study employs a quantitative approach using a quasi-experimental design with a Nonequivalent Control Group Design. The population consists of all fifth-grade students at SD Negeri 9 Songan for the 2025/2026 academic year, with a sample size of 47 students, comprising Class VA as the experimental group and Class VB as the control group. Data collection techniques included a reading interest questionnaire as well as Pretest and posttest assessments. Data analysis was conducted using normality tests and hypothesis testing via the t-test. The results of the study indicate that there was an increase in students’ reading interest in the experimental class after the implementation of the literacy-based PBL learning model. This is evidenced by the results of the hypothesis test, which showed a significant difference between the Pretest and posttest scores in the experimental class compared to the control class. Thus, it can be concluded that the literacy- based Problem-Based Learning model has a significant effect on increasing students’ reading interest.